Modified cisplatin/interferon α‐2b/doxorubicin/5‐fluorouracil (PIAF) chemotherapy in patients with no hepatitis or cirrhosis is associated with improved response rate, resectability, and survival of initially unresectable hepatocellular carcinoma. Issue 18 (2nd July 2013) - Kaseb, Ahmed O.; Shindoh, Junichi; Patt, Yehuda Z.; Roses, Robert E.; Zimmitti, Giuseppe; Lozano, Richard D.; Hassan, Manal M.; Hassabo, Hesham M.; Curley, Steven A.; Aloia, Thomas A.; Abbruzzese, James L.; Vauthey, Jean‐Nicolas
<x xml:space="preserve">Abstract</x> BACKGROUND The purpose of this study was to evaluate the factors associated with response rate, resectability, and survival after cisplatin/interferon α‐2b/doxorubicin/5‐fluorouracil (PIAF) combination therapy in patients with initially unresectable hepatocellular carcinoma. METHODS The study included 2 groups of patients treated with conventional high‐dose PIAF (n = 84) between 1994 and 2003 and those without hepatitis or cirrhosis treated with modified PIAF (n = 33) between 2003 and 2012. Tolerance of chemotherapy, best radiographic response, rate of conversion to curative surgery, and overall survival were analyzed and compared between the 2 groups, and multivariate and logistic regression analyses were applied to identify predictors of response and survival. RESULTS The modified PIAF group had a higher median number of PIAF cycles (4 versus 2, P = .049), higher objective response rate (36% versus 15%, P = .013), higher rate of conversion to curative surgery (33% versus 10%, P = .004), and longer median overall survival (21.3 versus 10.6 months, P = .002). Multivariate analyses confirmed that positive hepatitis B serology (hazard ratio [HR] = 1.68; 95% confidence interval [CI] = 1.08‐2.59) and Eastern Cooperative Oncology Group performance status ≥ 2 (HR = 1.75; 95% CI = 1.04‐2.93) were associated with worse survival whereas curative surgical resection after PIAF treatment (HR = 0.15; 95% CI = 0.07‐0.35) was associated with improved survival. CONCLUSIONS In patients with initially unresectable hepatocellular carcinoma, the modified PIAF regimen in patients with no hepatitis or cirrhosis is associated with improved response, resectability, and survival. Cancer 2013;119:3334–42 © 2013 American Cancer Society.